ANALISIS PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA KARYAWAN BIDANG OTOMOTIF) - Maranata, Bonaventura Hendrawan; Widyaningtyas, Dian Prasetyo (BBM (Buletin Bisnis & Manajemen), 2024)
This research aims to determine, explain and analyze the influence of Workload and Work Stress variables on Employee Performance (Case Study of Automotive Employees). This research was conducted using descriptive and verification methods. The sample in this study was 100 employees who worked in the automotive sector (motorcycle repair shop, car repair shop). The data collection technique used in this research was distributing questionnaires. Data analysis used in this research includes correlation analysis, multiple linear regression analysis, and scale range analysis.The results of this research at a significance level of 5% are, (1) Workload has a positive and significant effect on employee performance (2) Excessive work stress has an effect on employee performance (3) Workload and work stress simultaneously have a positive and significant effect of. This means that location and motivation variables contribute 61% to employee performance (case study of employees in the automotive sector), and the remaining 38.5% is the contribution made by other variables not mentioned in this research.Keywords: Workload, Job Stress, Employee Performance.